2018
DOI: 10.1007/s40264-018-0746-z
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and the Future of the Drug Safety Professional

Abstract: The healthcare industry, and specifically the pharmacovigilance industry, recognizes the need to support the increasing amount of data received from individual case safety reports (ICSRs). To cope with this increase, more healthcare and qualified professionals are required to capture and evaluate the data. To address the evolving landscape, it will be necessary to embrace assistive technologies such as artificial intelligence (AI) at scale. AI in the field of pharmacovigilance will possibly result in the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 1 publication
0
20
0
2
Order By: Relevance
“…Pharmacovigilance professionals must learn new skills and acquire technical knowledge relating to system implementation and CSV to remain successful in this rapidly advancing sector [ 18 ]. A once-siloed working paradigm is shifting, requiring pharmacovigilance professionals to understand business and technical requirements, to select representative data to adequately train and approve AI models, and to understand how, when, and why to retrain their models over time.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacovigilance professionals must learn new skills and acquire technical knowledge relating to system implementation and CSV to remain successful in this rapidly advancing sector [ 18 ]. A once-siloed working paradigm is shifting, requiring pharmacovigilance professionals to understand business and technical requirements, to select representative data to adequately train and approve AI models, and to understand how, when, and why to retrain their models over time.…”
Section: Discussionmentioning
confidence: 99%
“…Already, there is evidence that AI can equal or exceed human performance in various areas of medical science [47][48][49][50][51]. • Change management with impacted functions and individuals [52]. The PV system spans many areas beyond the safety department of the MAH, and the use of new IT will cause impact to many upstream and downstream stakeholders.…”
Section: Ethical and Policy Implications Of Automation Within Pv Systemsmentioning
confidence: 99%
“…Change management with impacted functions and individuals [ 52 ]. The PV system spans many areas beyond the safety department of the MAH, and the use of new IT will cause impact to many upstream and downstream stakeholders.…”
Section: Ethical and Policy Implications Of Automation Within Pv Systmentioning
confidence: 99%
“…Emerging research has indicated familial migraine contains a higher pathologic gene load associated with migraine than sporadic cases [32], while another study has begun to map possible loci containing genes involved in migraine pathology, specifically locating 38 new loci [15]. In addition to physiologic aspects, applications of high end computing are being utilized to analyze high volumes of drug safety data [33]. This approach utilizing personalized medicine has already been put into translational studies for cardiovascular anti-coagulant drugs, such as warfarin, which has highly variable therapeutic windows depending on the DNA variants encoding enzymes in its metabolic pathway.…”
Section: Future Direction Of Field and Precision Medicinementioning
confidence: 99%